Clinical efficacy and immunological mechanisms of sublingual and subcutaneous immunotherapy in asthmatic/rhinitis children sensitized to house dust mite: an open randomized controlled trial - AKKOÇ, TUNÇ (WILEY, 2010)
Background In children, the clinical efficacy and immunological mechanisms of sublingual immunotherapy (SLIT) compared with subcutaneous immunotherapy (SCIT) is still to be elucidated. Objectives To compare SLIT, SCIT and pharmacotherapy in relation to clinical efficacy and immunological mechanisms that govern its effect in asthmatic/rhinitis children who were sensitized to house dust mite (HDM). Methods In this single centre, prospective, randomized, controlled, open labelled, three parallel group trial, 48 patients mono-sensitized to HDM were randomized to receive either SLIT (n = 16), SCIT (n = 16) or pharmacotherapy alone (n = 16). Symptom, medication and visual analogue score (VAS) were collected and bronchial-nasal hyper-reactivity, skin prick tests, total-specific IgE were performed at baseline and 12 months after treatment. In addition, peripheral blood mononuclear cells were cultured with recombinant Der p 1 and Bet v 1 extracts and allergen-specific IL-4, IL-5, IL-13, IFN-gamma, IL-10, and TGF-beta secretions were measured. Results SLIT and SCIT demonstrated a significant reduction of total rhinitis and asthma symptom score, total medication score, VAS and skin reactivity to HDM (P<0.05) when compared with pharmacotherapy. A significant reduction of serum-specific HDM-IgE in SCIT and SLIT were observed. Moreover, titrated nasal provocative dose significantly increased in both immunotherapy groups when compared with the pharmacotherapy group. No adverse effects were reported in SLIT, while two patients demonstrated serious adverse events in SCIT. After 1 year of treatment, Der p 1-driven IL-10 significantly increased in SLIT compared with pharmacotherapy, whereas Bet v 1-driven TGF-beta (negative control) increased significantly in SLIT only. No changes were observed for Th1-Th2 cytokines. Conclusion Both SLIT and SCIT demonstrated clinical improvement compared with pharmacotherapy in asthma/rhinitis children sensitized to HDM.
Keywords: asthma; cytokines; nasal provocation; rhinitis; sublingual-subcutaneous immunotherapy; GRASS-POLLEN IMMUNOTHERAPY; T-REGULATORY CELLS; DOUBLE-BLIND; ALLERGIC CHILDREN; RHINITIS; ASTHMA; CHILDHOOD; CYTOKINE; INDUCTION; INCREASES